Light‐Induced Dimerization Approaches to Control Cellular Processes - Klewer, Laura (Chemistry, 2019)
Light‐inducible approaches provide a means to control biological systems with spatial and temporal resolution that is unmatched by traditional genetic perturbations. Recent developments of optogenetic and chemo‐optogenetic systems for induced proximity in cells facilitate rapid and reversible manipulation of highly dynamic cellular processes and have become valuable tools in diverse biological applications. New expansions of the toolbox facilitate control of signal transduction, genome editing, “painting” patterns of active molecules onto cellular membranes, and light‐induced cell cycle control. A combination of light‐ and chemically induced dimerization approaches have also seen interesting progress. Herein, an overview of optogenetic systems and emerging chemo‐optogenetic systems is provided, and recent applications in tackling complex biological problems are discussed.